Development of brain synchronisation within school-age: individual analysis of resting (alpha) coherence in a longitudinal data set - Gmehlin, Dennis; Thomas, Christine; Weisbrod, Matthias; Walther, Stephan; Resch, Franz; Oelkers-Ax, Rieke (Clinical neurophysiology, 2011)
Objective - Given evidence that synchronisation of neuronal activity may be a correlate of cognition, we examined EEG coherence as function of age and inter-electrode distance in healthy children and adolescents in order to elucidate basic information for a better understanding of developmental disorders associated with deficits in cognitive functions. - Methods - Based on a 64-channel eyes closed resting EEG we combined local and global coherence measures in order to reduce volume conduction and reference effects. We used a two point longitudinal design in order to analyze intraindividual change during school-age (n=40; 6-18years). Coherence was analyzed within individually adjusted frequency bands and around iPF (= individual alpha peak frequency). - Results - Both local and global resting coherence was largest in the alpha range and particularly around iPF. Local synchronisation was larger in the left compared with the right hemisphere. Controlling for increases in iPF, synchronisation increased with age, with global changes being most pronounced in the alpha range. Moreover age-related changes suggest an earlier development in girls. - Conclusions - Our data provides evidence that both local and global functional integration increases during normal development within school-age. - Significance - This general pattern - combined with more specific effects of sex and frequency - may help to specify deviations in developmental disorders.
Gesehen am 27.06.2022